Una”significant form” svelata L’allestimento della mostra” Italian Art” alla Royal Academy nella Londra del 1930 (Altre Modernità, 2011)
My essay argues with the Exhibition of Italian Art 1200-1900 at the Burlington fine Arts Club, made possible by Mussolini and Lady Ivy Chamberlain in 1930. It focuses on the development and deployment of the aesthetic display resources theorized by Roger Fry to enhance the visitors’ experience of the art work, unveiling a hidden structure in the rhythm of the art galleries. In the growing interest amongst curators, interpretation managers and designers exploring ways in which they can enhance public understanding of, and access to the arts and decorative arts, this study builds a frame into which display discourses might find a proper set and a parameter model. It highlights words spoken and written about Italian Art and its legacy in London and Italy during Fascism, exploring ways of organising the rooms and hanging the precious selected works of art, deploying distinctive aesthetic resources, designing a display with a ‘significant form’ able to enhance the impact of the vision of art, aiming to give London the highest emotion of art. Thanks to the display descriptions left by Haskell and Witt it is now possible to retrace a structure in the galleries design of this  very first blockbuster exhibition. It nourishes the debate on art display strategies and styles preserving national identity within the mood of postmodernism. It figures out a model that could be adapted or be inspiring for museum and galleries professionals today.
Keywords: Display and Interpretation; Curation; poetica dell’allestimento; architettura d’arte; idee per allestimenti; aesthetic display